VARIATION IN WOOD PHYSICAL PROPERTIES OF EUCALYPTUS GROWING IN SEEDLING SEED ORCHARD IN PLEIHARI, SOUTH KALIMANTAN - Susilawati, Siti; Marsoem, Sri Noegroho (Indonesian Journal of Forestry Research, 2006)
This study shows an effort to obtain the best performance of Eucalyptus pellita trees, which was conducted by examining the physical properties of wood of 116 months age Eucalyptus pellita trees. The trees of various families used in this study were all grown in Seedling Seed Orchard (SSO), Pleihari. A total of 10 families with 3 individual trees for each family as replication were randomly selected for the whole SSO.Â Â  Selected sample trees were felled, cut and divided into three different parts (bottom, middle and top) of the stem. Each stem part was then cut into wood samples running from pith to bark portion for the examination of its physical properties according to British Standard BS 373-1957. The collected data on those properties were analyzed by using a completely randomized design (CRD). The results showed that there were significant differences in wood density and fiber length among different height, and among wood sections from pith to bark in individual trees as well as among families. Wood density showed high family heritability (0.708) and genetic correlation between wood density and fiber length were significantly different (r = 0.543).